Meningkatkan Hasil Belajar Siswa Dengan Menerapkan Model Pembelajaran Kooperatif Tipe Teams Games Tournament - Hadiyanti Ulfah; M. Arifuddin Jamal; Mustika Wati (Universitas Lambung Mangkurat, 2013)
Hopkins Model Classroom Action Research as much as 3 cycles are done to improve student learning outcomes. This study describes (1) lesson plan, (2) learning outcomes, (3) social skills, (4) student responses. The results showed (1) lesson plan cycle I 80.00% (good), cycle II 85.00% (very good), and cycle III 91.99% (very good), (2) students' mastery first cycle 62.50%, 75.76% second cycle and third cycle of 87.88%, (3) the student's social skills first cycle 67.18% (good), cycle II 81.77% (very good), and cycle III 97.91% (very good), (4) the response of students in the learning using TGT type of cooperatif learning in good categori too. Retrieved conclusion that cooperative learning model type TGT can improve student learning outcomes.